2019
DOI: 10.33314/jnhrc.v0i0.1561
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Depression among Older People Living in a Community of Nepal

Abstract: Background: Loneliness and depression are the noteworthy mental health issues which are prevalent among older people but only a few studies have addressed this aspect especially in developing countries. So, this study is an attempt to shed light to this aspect of older adult’s life, in order to assess the level of loneliness and depression, to identify associated factors,and to find out the correlation between loneliness and depression.Methods: A descriptive cross-sectional study design was used to collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…This relationship is stronger because the elderly people who came to the family health centers are more alone in their social life and the fact that the elderly people who were hospitalized had hospital attendants together with them caused them to feel less lonely. In the studies conducted, a positive relationship was found between loneliness and depression 4,23,24 . It is stated that among the risk factors in the development of depression in elderly individuals, the feeling of loneliness felt with the decrease in social relations is one of the most important factors 19 …”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…This relationship is stronger because the elderly people who came to the family health centers are more alone in their social life and the fact that the elderly people who were hospitalized had hospital attendants together with them caused them to feel less lonely. In the studies conducted, a positive relationship was found between loneliness and depression 4,23,24 . It is stated that among the risk factors in the development of depression in elderly individuals, the feeling of loneliness felt with the decrease in social relations is one of the most important factors 19 …”
Section: Discussionmentioning
confidence: 98%
“…In a study examining the depression level of individuals aged 60 and over who were receiving inpatient treatment in the hospital, 69.1% of the individuals were found to score above the threshold value 3 . Female gender, chronic diseases, cognitive and functional impairment, personality traits, stressful life events, history of depression, sensory losses, social losses, insufficient activity, increased dependency level, insufficient support and loneliness are among the preparatory factors for depression 4‐7 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations